2023
DOI: 10.1002/ajoc.202300303
|View full text |Cite
|
Sign up to set email alerts
|

Recent Advances in Multicomponent Electro‐Organic (Electrochemical) Synthesis of Heterocycles

Abstract: In terms of pharmaceuticals and biological applications, synthesis of complex organic molecules is a significant and fast‐developing area. In this context, organic electrosynthesis is an alternative way to the traditional methods for chemo‐, regio‐, and stereoselective syntheses. Electro‐organic reactions occur at room temperature and normal pressure, through transferring electrons. It has been found that electrosynthesis is a mild approach for preparing electrophilic substrates, bases, and nucleophiles in sit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 71 publications
0
6
0
Order By: Relevance
“…It is worth noting that we recently published some interesting review articles regarding multicomponent reactions. 63,64 A novel series of coumarin-benzimidazole hybrids was obtained and their growth inhibitory effect (in vitro) was studied against six cancer cell lines (A549, H460, HT29, MKN-45, U87MG, and SMMC-7721) using foretinib as the standard reference. 65 The studies indicated that compounds 26a-d (Fig.…”
Section: Rsc Medicinal Chemistry Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…It is worth noting that we recently published some interesting review articles regarding multicomponent reactions. 63,64 A novel series of coumarin-benzimidazole hybrids was obtained and their growth inhibitory effect (in vitro) was studied against six cancer cell lines (A549, H460, HT29, MKN-45, U87MG, and SMMC-7721) using foretinib as the standard reference. 65 The studies indicated that compounds 26a-d (Fig.…”
Section: Rsc Medicinal Chemistry Reviewmentioning
confidence: 99%
“…It is worth noting that we recently published some interesting review articles regarding multicomponent reactions. 63,64…”
Section: Coumarin Hybridsmentioning
confidence: 99%
“…In this work, we have reviewed recent progress in multicomponent reactions using 5-aminotetrazole as a building block. 31 32 33 34 35 36 This article discusses 5-aminotetrazole as a key molecule in synthesizing heterocyclic compounds reported in the literature from 2017 to 2023.…”
Section: Introductionmentioning
confidence: 99%
“…31 Electrochemistry also provides precise control over reaction conditions, leading to improved selectivity and yield, thereby reducing the need for resource-intensive purification steps. 32 Additionally, electro-synthesis often involves the use of benign and readily available starting materials, contributing to the overall eco-friendliness of the process. As the demand for sustainable manufacturing practices continues to rise, electro-synthesis emerges as a promising avenue for achieving green chemistry objectives, paving the way for a more environmentally conscious and responsible approach to chemical synthesis.…”
Section: Introductionmentioning
confidence: 99%
“…This innovative technique leverages renewable energy sources, such as solar or wind power, to generate the required electrical energy, aligning with the principles of sustainability 31 . Electrochemistry also provides precise control over reaction conditions, leading to improved selectivity and yield, thereby reducing the need for resource‐intensive purification steps 32 . Additionally, electro‐synthesis often involves the use of benign and readily available starting materials, contributing to the overall eco‐friendliness of the process.…”
Section: Introductionmentioning
confidence: 99%